Do Environmental, Social, and Governance (ESG) Practices Improve Corporate Profitability? Evidence from European Companies - Tarin, Ilma Afrin (My University, 2026)
The thesis focuses on the correlation between Environmental, Social, and Governance (ESG) performance and corporate profitability of the publicly listed non-financial European companies in the period 2011-2024. The study relies on panel data available in the Refinitiv ESG and financial databases to estimate that ESG engagement improves the profitability of firms and its impact varies by ESG dimension, industry, and economic stress periods. The findings have shown that aggregate ESG performance is not positively correlated with short-term accounting-based profitability, and is, in certain specifications, negatively related to firm performance, indicating the existence of short-term implementation and compliance costs. The performance of governance turns out to be comparatively stronger than the performance of environment and social, whereas the performance of the environment and social turns out to be relatively weak and contingent. The sectoral analyses indicate high heterogeneity of the ESG-profitability relationships, which indicates the significance of industry contexts. In both crisis-interaction models of the COVID-19 pandemic and the European energy crisis, it is revealed that ESG performance does not consistently reduce short-term decreases in profitability during economic stress times. In general, the results indicate that ESG engagement is a short-term tradeoff between financial perspectives, as opposed to short-term profitability, and the financial relevance of ESG is also subject to ESG dimension, sector features, and economic circumstances.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance